Low carbohydrate diets and performance - Cook, Chad M.; Haub, Mark D. (My University, 2007)
Athletes are continually searching for means to optimize their performance. Within the past 20 years, athletes and scientists have reported and/or observed that consuming a carbohydrate restricted diet may improve performance. The original theories explaining the purported benefits centered on the fact that fat oxidation increases, thereby "sparing" muscle glycogen. More recent concepts that explain the plausibility of the ergogenicity of low carbohydrate, or high fat, diets on exercise performance pertain to an effect similar to altitude training. We and others have observed that, while fat oxidation may be increased, the ability to maintain high intensity exercise (e.g., above the lactate threshold) seems to be compromised or at least indifferent compared to when more carbohydrate was consumed. That said, clinical studies clearly demonstrate that ad-libitum low carbohydrate diets elicit greater decreases in body weight and fat than energy equivalent low fat diets, especially over a short duration. Thus, while low carbohydrate and high fat diets appear detrimental or indifferent relative to performance, they may be a faster means to achieve a more competitive body composition.
Keywords: Atkins Diet; South Beach Diet; Exercise; Whole-grain; Obesity; Low carbohydrate diets